Students Teams – Achievement Division (STAD) for enhancing speaking performance and teamwork satisfaction in English as a second language (ESL) classrooms - Izyan Safira Ibrahim,; Nor Hafizah Adnan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to examine students’ perceptions toward the use of the Students Teams – Achievement Division (STAD) in enhancing their English speaking performance. This study also investigated the extent to which teamwork satisfaction can beachieved through the application of STAD. STAD is a cooperative learning strategy that involves small groups of students with different levels of abilities collaborating to accomplish a shared learning goal. A total of 73 students in a government-funded national school in a suburban area of the district of Semenyih, Selangor, Malaysia were selected through purposive sampling in this study. Students were assigned to five or six-member heterogeneous groups, and a three-step cycle was initiated once the assignment of students was created. The three-step cycle included teaching, team study, and testing. Data was collected via a survey and a set of questionnaires was distributed to the students after applying STAD in their lessons for two months. The findings obtained provided evidence that students were generally positive about using STAD to enhance their speaking performance and teamwork satisfaction. Thus, it can be concluded from this study that STAD encourages students to actively participate in the classroom, build up their confidence, and improve their communication skills. It was therefore recommended that teachers should consider using STAD in teaching English and other content areas, utilizing students’ collaboration to enhance learning and maximize interaction among the group.